Answer:
The answer is: The y intercept form is: y = -2x - 7. The point slope form is:
y + 7 = -2(x - 0)
Explanation:
The equation to find the slope is:
m = (y - y1) / (x - x1)
Substitute in the given points (-5, 3) and (0, -7)
m = (3 - (-7)) / (-5 - 0)
m = (3 + 7) / -5
m = 10/-5 = -2
Now use the slope to form the intercept form of the equation, from the point-slope form:
y - (-7) = -2(x - 0)
y + 7 = -2x
y = -2x - 7
Proof:
Use (-5, 3) substitute -5 for x and verify that the answer is 3:
f(-5) = -2(-5) - 7 = 10 - 7 = 3